2019
DOI: 10.1038/s41467-019-10022-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MYC by the SMARCB1 tumor suppressor

Abstract: SMARCB1 encodes the SNF5 subunit of the SWI/SNF chromatin remodeler. SNF5 also interacts with the oncoprotein transcription factor MYC and is proposed to stimulate MYC activity. The concept that SNF5 is a coactivator for MYC, however, is at odds with its role as a tumor-suppressor, and with observations that loss of SNF5 leads to activation of MYC target genes. Here, we reexamine the relationship between MYC and SNF5 using biochemical and genome-wide approaches. We show that SNF5 inhibits the DNA-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(108 citation statements)
references
References 54 publications
7
98
3
Order By: Relevance
“…SMACB1 was commonly downregulated in HF, KF, and KP. SMACB1 is a core subunit of the SWI/SNF (BAF) chromatin-remodeling complex and is well-recognized as a tumor suppressor gene, which is inactivated in aggressive cancers such as nearly all pediatric rhabdoid tumors [ 28 , 29 ]. These highly regulated common genes represent the typical gene signatures of various cells and nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…SMACB1 was commonly downregulated in HF, KF, and KP. SMACB1 is a core subunit of the SWI/SNF (BAF) chromatin-remodeling complex and is well-recognized as a tumor suppressor gene, which is inactivated in aggressive cancers such as nearly all pediatric rhabdoid tumors [ 28 , 29 ]. These highly regulated common genes represent the typical gene signatures of various cells and nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Carugo et al reported that the Myc-p53 axis regulates cellular proteostasis in SMARCB1-deficient malignant rhabdoid tumors [27]. Additionally, the SNF5 subunit encoded by SMARCB1 has been identified as an inhibitor that prevents the DNA-binding ability of Myc [26]. Together, these findings suggest that SMARCB1 deficiency is associated with an increased rate of protein synthesis and Myc activity in ATRTs, particularly in Myc-ATRTs, which may explain their high sensitivity to BTZ.…”
Section: Discussionmentioning
confidence: 98%
“…These results further support the link between Myc and protein synthesis in ATRT cells. Moreover, the correlation of Myc activity and SMARCB1-deficient cancers has been identified in priors studies [26][27][28]. Alimova et al found that SMARCB1-deficient ATRTs expressed higher Myc activity compare to normal brain tissues, regardless of the subtypes of ATRTs [28].…”
Section: Discussionmentioning
confidence: 98%
“…This experimental finding is backed by studies in primary tumours, which found an overexpression of SHH components in a subgroup of ATRT [25]. Not only MYC‐dependent signalling but also the expression of MYC itself are also repressed by an intact SWI/SNF complex [54,55].…”
Section: Three Of a Kind? Structure And Functions Of Three Baf Complexesmentioning
confidence: 98%